Modelo Ecuatoriano de Equilibrio General Aplicado Refinamiento del Mercado Laboral - Sánchez A., Leonardo (2005)
This paper studies the relationship between trade liberalization and the labor market. It is often claimed that increased foreign competition in developing countries leads to an expansion of the informal sector, defined as the sector that does not comply with labor market legislation. Based on the applied? general equilibrium model developed by the Central Bank of Ecuador the concept of efficiency wages is included to analyze the effects of the Free Trade Agreement (FTA) between Ecuador and the United States. The paper presents evidence that trade liberalization leads to an increase in the formal labor demand, but with rising inequality.